Sistem Informasi Jurnal Transaksi dan Angsuran Properti Berbasis Syariah - Apriyanti, Linda; Fernanda, Devanska Irsan (Jurnal Bangkit Indonesia, 2025)
The recording of transactions and installments in Indonesia's property business still largely relies on manual spreadsheet-based methods, which are prone to data loss, recording errors, and limited accessibility. This study aims to design and develop a Sharia-Based Property Transaction and Installment Journal Information System to improve recording efficiency and ensure compliance with Sharia principles in property sales transactions. The system was developed using the Rapid Application Development (RAD) method, utilizing Unified Modeling Language (UML) and Entity Relationship Diagram (ERD) for modeling, along with MySQL and CodeIgniter as the development platform. Testing using the Black Box Testing method demonstrated that key features, such as transaction journal recording, chart of account management, installment payments, and transaction monitoring, function effectively. The study results indicate that this system can enhance transaction recording efficiency, simplify installment payment tracking, and ensure that all financial processes comply with Sharia standards. By implementing this system, Sharia-compliant property businesses are expected to manage their finances more transparently, securely, and efficiently.